INSTITUTIONALIZING OF PROPERTY RELATIONS IN THE SYSTEM OF NETWORK COORDINATION NEXUS - D. Mokichev, Sergey; F. Zulfakarova, Lilia; M. Vakhitova, Tina (Gênero & Direito, 2019)
There is an active development and use of the principles and research tools of the institutional approach in modern economic science. It allows establishing the relationships that exist between the economic, political and social elements of the system, expanding the boundaries of economic life. The institutional environment determines the goals, functions and dynamics of interaction in property relations. Thus, it appears the effectiveness of functioning of its various forms, which will depend on the institutional structure of management as a system of norms and rules that determine the configuration of property rights, together with coercive instruments. The article considers the approach from the theory of constructivism, which describes the structural features of property relations, taking as a basis the system of network coordination of relations. Formation of a network structure and a new, non-hierarchical way of coordinating ties reflects new economic realities associated with the strong interdependence of property subjects. Formation of a knowledge economy, development of globalization, integration of property subjects have led to the accelerated development of innovations, to a new quality of property relations. Innovations are supported by a huge agglomeration of social, innovative, intellectual and financial capital, which forms the emergence of “innovations in innovations” and determines the relevance of studying the system of network coordination of relations.